LAPAROSCOPIC SLEEVE GASTRECTOMY - A PROSPECTIVE FOLLOW UP OF 30 PATIENTS - Toor, Asad Ali; Farooka, Muhammad Waris; Ayyaz, Mahmood; Razzaq, Zeeshan; Malik, Awais Amjad; Nawaz, Allah; Mahmood, Asif; Redmond, Henry Paul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Morbid obesity has become a surgically treatable problem. Laparoscopic sleeve gastrectomy is becoming a popular choice both for surgeons and patients due to effectiveness and low complication rates. Methods: It was a prospective case series spanning over 6 years. Patient enrolment started from January 2009 and data collection completed in January 2015. Patient with BMI (weight in kilogram/height in meter square) of more than 35 were included in the study. Follow up was at 2 weeks, 1 month, 6 months and 12 months. Success was defined as 25% of excess weight loss at 1 year. Paired t-test was used as a test of significance. Results: A total of 34 patients were included in the study over a 6-year period, 3 were lost to follow up and one patient died of cardiac arrest. Data of 30 patients is considered for final analysis. Mean age was 39.5±10 years, while mean BMI 45.8±6.3 (range 37.1-62.2). Average weight of the patients pre-operatively was 129.9±20.8 kg while mean excess weight was 70.3±20.8 kg. Average weight loss at two weeks was 8.9±2.9 kg, at one month 14.7±4.6 kg, at 6 months 25.0±7.6 kg and at twelve months was 31.4±6.8 kg. Mean percentage of excess weight loss after 2 weeks was 13.5±4.6%, at one month 22.0±6.1%, at six months 37.6±12.0% and at twelve months 47.3±10.1%. Conclusion: Laparoscopic sleeve gastrectomy is an effective weight loss surgery with minimal complications. On average weight loss of about 30 kg at one year was achieved which equals to almost half of excess body weight. Keywords: Obesity; Weight loss surgery;Sleeve Gastrectomy